Soil Carbon Dioxide Flux Partitioning in a Calcareous Watershed With Agricultural Impacts. Issue 10 (5th October 2021) - Hodges, Caitlin; Brantley, Susan L.; Sharifironizi, Melika; Forsythe, Brandon; Tang, Qicheng; Carpenter, Nathan; Kaye, Jason
Abstract: Predicting the partitioning between aqueous and gaseous C across landscapes is difficult because many factors interact to control carbon dioxide (CO2 ) concentrations and removal as dissolved inorganic carbon (DIC). For example, carbonate minerals buffer soil pH and allow CO2 dissolution in porewaters, but nitrification of fertilizers may decrease pH so that carbonate weathering results in a gaseous CO2 efflux. Here, we investigate CO2 partitioning in an agricultural, first‐order, mixed‐lithology humid, temperate watershed. We quantified soil mineralogy and measured porewater chemistry, soil moisture, and soil pCO2 and pO2 as a function of depth at three hillslope positions. Variation of soil moisture along the hillslope was the dominant control on the concentration of soil CO2, but mineralogy acted as a secondary control on the partitioning of CO2 between gaseous and aqueous phases. Regression slopes of pCO2 versus pO2 in the carbonate‐bearing soils indicate a deficit of aerobically respired CO2 relative to O2 ( p < 0.05). Additionally, nitrification of upslope fertilizers did not lower soil pH and therefore did not cause a gaseous CO2 flux from carbonate weathering. We concluded that in the calcareous soils, up to 43% of respired C potentially dissolves and drains from the soil rather than diffusing out to the atmosphere. To explore the possible implications of the reactions we evaluated, we used databases of carbonate minerals and land uses to map types of soil degassing behaviors. Based on our maps, the partitioning of respired soil CO2 to the aqueous phase could be important in estimating ecosystem C budgets and models. Plain Language Summary: Carbon dioxide (CO2 ) produced by roots and microbes in soil is a key component of the global carbon cycle. Respired CO2 exits soil as a gas but also dissolves in soil porewaters during weathering reactions in soils. These reactions reduce the amount of CO2 exiting the soil surface. Conversely, agricultural nitrogen inputs may shift the release of CO2 into the gas phase. We investigated when these reactions may be important in affecting CO2 flux from the soil surface. In soils containing carbonate minerals, we found that respired CO2 drove weathering of carbonate minerals and decreased the amount of CO2 that degasses from the soil surface by up to 43%. We found no evidence of agricultural land use driving CO2 from carbonate minerals into the gas phase. Our results indicate that measurements of soil surface CO2 flux measurements would underestimate the amount of CO2 produced by plant roots and microbes if the aqueous fluxes are ignored. These reactions are common in soils and should be accounted for in soil C cycle models. Key Points: Carbonate mineralogy increases the dissolved inorganic carbon (DIC) flux out of soils in an agricultural, humid temperate watershed This flux of DIC could represent up to 43% of all respired carbon dioxide in the study soil that contains the most carbonates Surface carbon dioxide efflux measurements would substantially underestimate soil respiration rates in this watershed